To solve the equation 7y + 2 = 3y - 10, we can begin by isolating the variable y on one side of the equation.
First, we can subtract 3y from both sides of the equation to eliminate the 3y term on the right side of the equation:
7y + 2 - 3y = 3y - 10 - 3y
Simplifying this expression gives:
4y + 2 = -10
Next, we can subtract 2 from both sides of the equation:
4y + 2 - 2 = -10 - 2
This simplifies to:
4y = -12
Finally, we divide both sides of the equation by 4 to solve for y:
4y/4 = -12/4
This simplifies to:
y = -3
Therefore, the solution to the equation 7y + 2 = 3y - 10 is y = -3.
7y+2=3y-10
1 answer